(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
A network is defined as a set of nodes that are associated with a way to handle and transfer data and messages from source to destination. The congestion in the network occurs when a lot of traffic occurs, leads to delay, packet loss, bandwidth degradation, and high network overhead. Load balancing algorithms have been designed to reduce congestion in the network. Load Balancing is the redistribution of workload between two or more nodes to be executed at the same time. Two policies of load balancing algorithms: static and dynamic load balancing. This paper proposes a load balancing algorithm based on the hybrid (static and dynamic) policy using Network Simulator (version 2). The hybrid policy is used to improve network performance by redistributing the load between overloaded nodes to other nodes that are under loaded when congestion occurs. The simulation results show that the proposed algorithm used performance of the network with regard to throughput, packet delivery ratio, packet loss and the end-to-end delay.